Percepción de calidad y satisfacción de usuarios de una biblioteca de ciencias físicas. El caso de la Universidad Nacional Mayor de San Marcos - Guerra Caballero, Daniel Antonio (2024)
Objective. The research pretends to determinate the relationship between the quality of the services and the degree of satisfaction of the users of the specialized library of physical sciences “Rafael Dávila Cuevas” of the Physical Sciences Faculty of the National Major University of San Marcos in Lima,  Peru. Methods. Users responded to the LibQual+ and ACSI questionnaires to determine their perception of the quality of the library services and their level of satisfaction. Results. It was determined that the level of perception of quality and satisfaction is mostly average and the lowest valued was the dimension called “library as space”. Conclusions. It was concluded that there is a correlation between the quality of the service and the satisfaction of users, even if it is of a low type, because the service provided by the staff is the best rated.